Avaliação da atividade e mecanismo de ação antiúlcera gástrica do extrato hidroetanólico da entrecasca do caule de Virola elongata (Benth.) Warb - Almeida, Guilherme Vieira Botelho de (2016)
Virola elongata (Myristicaceae) is a native tree, but not endemic to Brazil, popularly known as “mucuíba”, “bicuíba” or “ucuúba” whose stem bark is traditionally used in the form of macerate or infusion by riverine populations for the treatment of gastric ulcers. The present work aimed to evaluate the toxicity, activity and possible mechanism of action of the hydroethanolic extract of the stem bark of V. elongata (HEVe), as well as to analyze the phytochemical composition of the extract. HEVe was obtained by maceration of the stem bark powder in 70% hydroethanolic solution (1:10, w/v). Phytochemical analysis was carried out by phytochemical screening, revealing the presence of phenolic compounds, flavonoids, alkaloids and phytosterols, followed by identification of the secondary metabolites rutin, catechin and gallic acid through high- performance liquid chromatography (HPLC). Acute toxicity of HEVe was evaluated by the Hippocratic assay with a single dose of 2,000 mg/kg b.w. on Swiss mice, which presented increased relative weight of the spleen in female mice and of the stomach for males, even though no macroscopic anomalies were present, as well as a reduction in weight gain for HEVe treated male mice. The difference found between both genders may be related the effect of lignans on hormonal levels. Cytotoxicity assay using hamster ovary cells (CHO-k1) and gastric adenocarcinoma cells (AGS) indicate that HEVe can be considered as non-cytotoxic in treatments of 24 and 72 h (IC50 > 200 μg/mL). On the micronucleus assay, used to evaluate genotoxic potential, HEVe was shown to be non-genotoxic. Antiulcerogenic activity of HEVe was evaluated through animal models of ulcer induced by acidified ethanol, in mice, piroxicam and by hypothermic restraint stress in Wistar rats, as well as the antiulcer activity of HEVe via acetic acid induced chronic ulceration model. In all tested models of activity, HEVe XVIII presented potent gastroprotective effects. In order to determine of the possible mechanisms of action of HEVe, its effects over gastric acid secretion in Shay’s pyloric ligation model, the mucogenic activity through Alcian Blue method, the participation of nitric oxide (NO) on the gastroprotective mechanism of action, the activity of myeloperoxidase (MPO), catalase (CAT), concentrations of interleulkin-10 (IL-10), tumor necrosis factor-α (TNF-α) interleukin-1β (IL-1β) in mice gastric tissue homogenate were evaluated. The mechanism of action by which HEVe exerts its effects seem to be independent form mucogenic action, but involving reduction of total acidty and volume of gastric content, NO activity, the modulation of the expression of TNF-α and stimulation of tissue repair, as well as reducing MPO and CAT activity, indicating reduction on the concentration of tissue reactive oxygen species. The results obtained in this study validate the use of the stem bark of V. elongata by the riverine population of Mato Grosso, however, further studies are necessary to elucidate the gastroprotective mechanism of action and the subchronic toxic potential of HEVe.